Taguchi Experimental Design for Optimization of Recombinant Human Growth Hormone Production in CHO Cell Lines and Comparing its Biological Activity with Prokaryotic Growth Hormone - Aghili, Zahra Sadat; Zarkesh-Esfahani, Sayyed Hamid (Drug Research, 2018)
Growth hormone deficiency results in growth retardation in children and the GH deficiency syndrome in adults and they need to receive recombinant-GH in order to rectify the GH deficiency symptoms. Mammalian cells have become the favorite system for production of recombinant proteins for clinical application compared to prokaryotic systems because of their capability for appropriate protein folding, assembly, post-translational modification and proper signal. However, production level in mammalian cells is generally low compared to prokaryotic hosts. Taguchi has established orthogonal arrays to describe a large number of experimental situations mainly to reduce experimental errors and to enhance the efficiency and reproducibility of laboratory experiments.In the present study, rhGH was produced in CHO cells and production of rhGH was assessed using Dot blotting, western blotting and Elisa assay. For optimization of rhGH production in CHO cells using Taguchi method An M16 orthogonal experimental design was used to investigate four different culture components. The biological activity of rhGH was assessed using LHRE-TK-Luciferase reporter gene system in HEK-293 and compared to the biological activity of prokaryotic rhGH.A maximal productivity of rhGH was reached in the conditions of 1%DMSO, 1%glycerol, 25 µM ZnSO4 and 0 mM NaBu. Our findings indicate that control of culture conditions such as the addition of chemical components helps to develop an efficient large-scale and industrial process for the production of rhGH in CHO cells. Results of bioassay indicated that rhGH produced by CHO cells is able to induce GH-mediated intracellular cell signaling and showed higher bioactivity when compared to prokaryotic GH at the same concentrations.
Keywords: Mammalian cell lines; Taguchi method; growth hormone; optimization; biological activity